A growth-coupling strategy for improving the stability of terpenoid bioproduction in Escherichia coli - Jing Chong Tan; Qitiao Hu; Nigel S. Scrutton (Microbial Cell Factories)
Abstract Background Achieving cost-competitiveness remains challenging for industrial biomanufacturing. With whole-cell biocatalysis, inefficiency presents when individual cells vary in their production levels. The problem exacerbates when the basis for such production heterogeneity is heritable. Here, evolution selects for the low- and non-producers, as they have lowered/abolished the cost of bioproduction to fitness. With the scale of population expansion required for industrial bioproduction, the asymmetrical enrichment can be severe enough to compromise the performance, and hence commercial viability of the bioprocess. Clearly, addressing production heterogeneity is crucial, especially in improving the stability of bioproduction across the cell generations. In this respect, we designed a growth-coupling strategy for terpenoid bioproduction in Escherichia coli. By knocking out the native 1-deoxy-D-xylulose 5-phosphate reductoisomerase (dxr) gene and introducing the heterologous mevalonate pathway, we created a chassis that relies solely on the latter for synthesis of all terpenoids. We hypothesise that the need to sustain the biosynthesis of endogenous life-sustaining terpenoids will impose a minimum level of productivity, which concomitantly improves the bioproduction of our target terpenoid. Results Following the confirmation of lethality of a dxr knockout, we challenged the strains with a continuous plasmid-based bioproduction of linalool. The Δdxr strain achieved an improved productivity profile in the first three days post-inoculation when compared to the parental strain. Productivity of the Δdxr strain remained observable near the end of 12 days, and after a disruption in nutrient and oxygen supply in a separate run. Unlike the parental strain, the Δdxr strain did not evolve the same deleterious mutations in the mevalonate pathway, nor a viable subgroup that had lost its resistance to the antibiotic selection pressure (a plausible plasmid loss event). We believe that this divergence in the evolution trajectories is indicative of a successful growth-coupling. Conclusion We have demonstrated a proof of concept of a growth-coupling strategy that improves the performance, and stability of terpenoid bioproduction across cell generations. The strategy is relatively broad in scope, and easy to implement in the background as a ‘fail-safe’ against a fall in productivity below the imposed minimum. We thus believe this work will find widespread utility in our collective effort towards industrial bioproduction.